УСТРІЙ УКРАЇНСЬКИХ ПРАВОСЛАВНИХ ЄПАРХІЙ:ТРАДИЦІЙНІ ЗАСАДИ І НАПРЯМ ЕВОЛЮЦІЇ (кінець XVІII – середина ХІХ ст.) (Zaporizhzhia Historical Review, 2021)
The author analyses the nature and results of the national-political pressure of the Russian imperial structure on the orthodox environment in Ukraine in the period from the end of the XVІII to the middle of the XIX century. They are defined as the dependent from the power and duration of the Russian national domination, the peculiarities of the modernization of the empire and the spread of the new social movements. The special attention is paid to the factor of the saving of the national traditions and to the process of the Ukrainian rebirth, which became more and more powerful.